International Encyclopedia for Labour Law and Industrial Relations - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1980)
This article reviews the book, "International Encyclopedia for Labour Law and Industrial Relations," by Roger Blanpain, Edited.